Hyperinsulinemia/Diabetes, Hearing, and Aging in the University of Wisconsin Calorie Restriction Monkeys - Fowler, Cynthia G. (Hear Res, 2015)
The purpose of this study was to determine the effects of hyperinsulinemia/Type 2 diabetes mellitus (HI-T2DM) on hearing impairment using rhesus monkeys to obtain control over diet and lifestyle factors that confound human studies. The study is a retrospective evaluation of rhesus monkeys from the Wisconsin National Primate Research Center (WNPRC) study on caloric restriction and aging. The research questions were the following: 1. Is HI-T2DM related to hearing impairment? 2. If so, what is the site of lesion in the auditory system? and 3. What physiological factors affect the risk of hearing loss in HI-T2DM? Three groups of eight monkeys each were matched by sex and age; the caloric restricted (CR) monkeys had a reduced risk of diabetes, the normal control (NL) group had a normal risk, and the hyperinsulinemia/diabetes (HI-D) group had already developed HI-T2DM. Auditory testing included distortion product otoacoustic emissions (DPOAEs) with f2 frequencies from 2211–8837 Hz and auditory brainstem responses (ABRs) obtained with clicks and tone bursts (8, 16, and 32 kHz). DPOAEs had signal-to-noise ratios 8–17 dB larger in the NL group than in the HID and CR groups, signifying that cochlear function was best in the NL group. ABR thresholds were 5–8 dB better in the NL group than in the HI-D group, although no significant differences across the groups were evident for the thresholds, latencies, interwave intervals, or amplitudes. Correlations were significant for quadratic relations between body mass index (BMI) and DPOAE, with largest DPOAEs for animals in the middle of the BMI range. ABR thresholds elicited with 16 and 32 kHz signals were significantly correlated, positively with BMI and HbA1c, and negatively with K(G) (glucose tolerance), S(I) (insulin sensitivity index) and DI (disposition index). These findings suggest that the hearing loss associated with HI-T2DM is predominantly cochlear, and auditory structures underlying the higher frequencies are at risk with HI-T2DM. Loss of auditory function begins in the hyperinsulinemia, pre-diabetic state.